2013
DOI: 10.1037/a0034095
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating power: Agenda ordering and the willingness to negotiate in asymmetric intergroup conflicts.

Abstract: In this research, we investigated how group power influences the way members of groups in asymmetrical conflict approach intergroup negotiations. Drawing on theories of negotiations and of intergroup power, we predicted that group power would interact with features of the proposed negotiating agenda to influence willingness to come to the table. Based on the negotiation literature, we focused on 2 types of sequential negotiation agendas: 1 beginning with the discussion of consequential issues before less conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 70 publications
1
45
2
1
Order By: Relevance
“…A 2 (population: Israeli vs. Palestinian) × 2 (target: Israeli vs. Palestinian) × 2 (motive: love vs. hate) ANOVA combining data from studies 2 and 3 confirms this difference, revealing a three-way population × target × motive interaction [F(1, 1,620) = 920.90, P < 0.0001, η (This effect and all others for which the results of Box's test for equality of covariance matrices were significant across studies are unchanged compared with assuming sphericity.) It might be the case that in asymmetrical conflicts, for groups such as these Palestinians, who experience oppression and have relatively less power than Israelis, expressions of anger and hatred (in attempts to change the status quo) are more normative (17,18). Nonetheless, these findings yet again represent a fundamental discrepancy between perceptions of one's ingroup's motives for conflict and perceptions of one's outgroup's motives for conflict.…”
Section: Significancecontrasting
confidence: 47%
See 1 more Smart Citation
“…A 2 (population: Israeli vs. Palestinian) × 2 (target: Israeli vs. Palestinian) × 2 (motive: love vs. hate) ANOVA combining data from studies 2 and 3 confirms this difference, revealing a three-way population × target × motive interaction [F(1, 1,620) = 920.90, P < 0.0001, η (This effect and all others for which the results of Box's test for equality of covariance matrices were significant across studies are unchanged compared with assuming sphericity.) It might be the case that in asymmetrical conflicts, for groups such as these Palestinians, who experience oppression and have relatively less power than Israelis, expressions of anger and hatred (in attempts to change the status quo) are more normative (17,18). Nonetheless, these findings yet again represent a fundamental discrepancy between perceptions of one's ingroup's motives for conflict and perceptions of one's outgroup's motives for conflict.…”
Section: Significancecontrasting
confidence: 47%
“…(response options: not willing at all = 1, somewhat not willing = 2, somewhat willing = 3, very willing = 4, don't know/not applicable = excluded from analysis) (adapted from ref. 17).…”
Section: Methodsmentioning
confidence: 99%
“…Group B were said to feel wronged by their situation, and to have been engaging in both violent and nonviolent resistance efforts in order to improve their situation, efforts which had scored some successes. Previous research had shown that assignment into the high vs. low power group in this scenario had psychological consequences (i.e., differentially influencing the RUNNING HEAD: HIERARCHY IN THE EYE OF THE BEHOLDER 30 conditions under which individuals were willing to negotiate with the other side; Kteily et al, 2013).…”
Section: Study 2 Methodsmentioning
confidence: 98%
“…We assessed willingness to negotiate with Palestinians using two items adapted from [26]: “How willing would you be for Israel to negotiate with a Palestinian side led by Mahmoud Abbas?” and “How willing would you be for Israel to enter direct negotiations involving Hamas in order to reach a final settlement?” Participants provided responses on Likert scales anchored at 1 (‘Not at all’) and 7 (‘Very much so’) ( r = .47, p < .001).…”
Section: Methodsmentioning
confidence: 99%